Association of Self-Reported Disease Severity with Depression and Anxiety among COPD Patients - Aldabayan, Yousef Saad; Alaban, Antonieto; Fabella, Eduardo; Abdelhameed, Amal Ismael (UI Scholars Hub, 2024)
Background: This study was conducted to estimate the proportion of patients who experience a high impact from chronic obstructive pulmonary disease (COPD) on their health status and those who also experience symptoms of depression and anxiety. It also sought to determine whether the health impact of the disease is associated with anxiety and depression. Methods: An analytical cross-sectional study was conducted among 177 randomly selected patients with COPD seeking treatment in various primary health centers in Al Ahsa, Saudi Arabia. The COPD Assessment Test (CAT) was used to determine the impact of COPD on health generally, and the Hospital Anxiety and Depression Scale was used to determine the presence of anxiety and depression symptoms. Multiple logistic regression was performed to determine the association between the health impact of COPD on the respondents and the presence of symptoms of anxiety and depression. Results: Patients who had a CAT Score of >21 were 17.37 times more likely to experience anxiety. Patients with COPD who had a CAT Score of >21 were 5.62 times more likely to experience depression. Conclusion: COPD had a severe impact on the health of nearly 30% of the patients affected. The high impact of COPD on health increases the likelihood of having anxiety and depression symptoms.